2020
DOI: 10.5582/irdr.2020.01027
|View full text |Cite
|
Sign up to set email alerts
|

Benign adrenal and suprarenal retroperitoneal schwannomas can mimic aggressive adrenal malignancies: case report and review of the literature

Abstract: The suprarenal retroperitoneum and adrenal gland is a rare site of origin for benign schwannomas which frequently present as larger and more aggressive lesions than schwannomas identified elsewhere. These tumors are often surgically excised. We present a case of an 81-year-old asymptomatic man presenting with an incidental 10 cm left suprarenal retroperitoneal mass identified on CT. The mass was indiscernible from the adrenal gland, demonstrating heterogeneous enhancement with a centrally cystic/necrotic core,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…Hormonal inactivity of these masses may not be helpful to clinicians for their differential diagnosis; nevertheless, imaging findings may confuse clinicians for preoperative diagnosis. Heterogeneous imaging findings such as thick walls, mixed cystic solid components, calcification, and necrosis may cause suspicion of pheochromocytoma and adrenocortical carcinoma ( 5 ). In MRI studies, intensity characteristics of adrenal schwannomas may be low in T1-weighted images and high in T2-weighted images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hormonal inactivity of these masses may not be helpful to clinicians for their differential diagnosis; nevertheless, imaging findings may confuse clinicians for preoperative diagnosis. Heterogeneous imaging findings such as thick walls, mixed cystic solid components, calcification, and necrosis may cause suspicion of pheochromocytoma and adrenocortical carcinoma ( 5 ). In MRI studies, intensity characteristics of adrenal schwannomas may be low in T1-weighted images and high in T2-weighted images.…”
Section: Discussionmentioning
confidence: 99%
“…Adrenal schwannomas may be confused with adrenocortical cancer, adrenal metastasis, or pheochromocytoma due to their imaging findings ( 5 ). In this case series, we present characteristics, preoperative clinical, radiologic, and postoperative findings of three different adrenal schwannomas with suspicious findings in imaging studies for malignancy or pheochromocytoma; however, after adrenal surgery, the diagnosis of benign adrenal schwannoma was revealed in pathological evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of AS during pregnancy has been reported in the literature. Retroperitoneal schwannoma can mimic the characteristics of female genital masses during pregnancy, such as adnexal mass, ectopic pregnancy, and so on ( 11 ). However, because we cannot use contrast media during pregnancy, this will make our diagnosis more difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Benign schwannoma has a good prognosis, but there is the possibility of recurrence and malignant transformation. Wilson et al ( 11 ) recently reviewed and identified 121 reported ASs in the literature, of which the average size of the tumor was about 6.5 cm, about 50% of the reported cases had punctate calcification, and about 50% of the cases showed cystic/necrotic changes on imaging. In our case group, the incidence of tumor necrosis/cystic changes in imaging findings was 87.5%, which was much higher than the average level.…”
Section: Discussionmentioning
confidence: 99%